PENGEMBANGAN SISTEM SERTIFIKASI BERBASIS JAMINAN MUTU DAN KEAMANAN PANGAN PRODUK UDANG EKSPOR - Santoso Santoso; Hatrisari Hardjomidjojo; John Haluan; Sugeng Hari Wisudo (Institut Pertanian Bogor, 2009)
The export value of total fish was US 2.258 billions in 2007 and shrimp contributed US 1,029 billions. Export shrimp products have to comply with requirements defined by importing countries, such as USA and European Union. Several problems of Indonesia exports shrimp, such as detentions upon arrivals in importing countries has challenged to improve export shrimp product. Laboratory analysis on contaminants, such as Escherichia coli, nitrofurans and sensory evaluation of shrimps throught out chains of production was performed. Existing system such as implement-tations of Standard Sanitation Operational Procedures (SSOP) and Hazard Analysis Critical Control Point (HACCP) during production chains of shrimp were verified. Existing system would not yet perform efectively to prevent detention of shrimp product, since certification system has not been implemented holistically. Good handling practices (GHP) at both fishing vessells and collection places have not been in place. Improvement of the certification system covering SSOP,GHP/Good Aquaculture Practice, and HACCP implementation, monitoring for contami-nants, process inspection, and final product inspection on production from ponds to processing units has been developed. Health Ccertificate for export shrimp is issued based on monitoring for contaminants, process inspection and necessary laboratory analysis as a holistic and integrated system.